2017
DOI: 10.3390/cosmetics4020018
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Skin-Aging Activity of a Standardized Extract from Panax ginseng Leaves In Vitro and In Human Volunteer

Abstract: Ginseng leaves contain high saponin composition and content, but are used less often than the root part. To develop a use for the leaves that exploits their properties, we studied ginseng leaves as the raw material of anti-aging cosmetics. This study highlights an assessment of the cellular factivity and clinical efficacy of ginseng leaf extract, providing necessary information relevant to the development of new cosmetic products. Panax ginseng leaf purified extracts (PGLE) were shown to have high contents of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 26 publications
0
6
0
1
Order By: Relevance
“…In both East Asian and Western countries, people have become increasing interested in maintaining a healthy skin. This has led to ongoing studies focused on the anti-wrinkle effects of a mixture of substances that have been reported to be associated with the key factors of skin aging such as inflammation, collagen synthesis, oxidative stress, and UV stress (Table S8) [241,242]. For instance, studies have reported on the cases where an intake of the mixture containing soy isoflavones, lycopene, vitamin C, vitamin E, and omega 3 fatty acid produced positive effects on facial wrinkle improvement [243].…”
Section: Reduced Inflammation and Skin Cell Protection In Wound Tissuementioning
confidence: 99%
“…In both East Asian and Western countries, people have become increasing interested in maintaining a healthy skin. This has led to ongoing studies focused on the anti-wrinkle effects of a mixture of substances that have been reported to be associated with the key factors of skin aging such as inflammation, collagen synthesis, oxidative stress, and UV stress (Table S8) [241,242]. For instance, studies have reported on the cases where an intake of the mixture containing soy isoflavones, lycopene, vitamin C, vitamin E, and omega 3 fatty acid produced positive effects on facial wrinkle improvement [243].…”
Section: Reduced Inflammation and Skin Cell Protection In Wound Tissuementioning
confidence: 99%
“…1 filter paper (Camlab, Cambridge, UK). V. vinifera seeds [12,13], M. oleifera leaves [14,15], and P. ginseng leaves and rhizomes [16,17] were extracted with 70% ethanol, whereas A. galanga leaves and rhizomes were extracted with 95% ethanol [18,19]. Each sample was concentrated using a rotary evaporator (Model Heidolgh VV2000, Heidolph Instruments Gmbh, Schwabach, Germany).…”
Section: Preparation Of Plant Extractsmentioning
confidence: 99%
“…Comprehensive investigations have determined that ginseng has many pharmacological effects on the immune, cardiovascular, endocrine, and central nervous systems [1]. The extracts isolated from Panax ginseng or P. quinquefolium (American ginseng) have been found to demonstrate anti-aging, anti-stress, anti-fatigue, and hepatoprotective properties [1,2,3].…”
Section: Introductionmentioning
confidence: 99%